Foot disease and physical function in older adults: A systematic review and meta‐analysis. (13th December 2020) - Iseli, Rebecca K.; Lee, Elton K; Lewis, Ellen; Duncan, Gregory; Maier, Andrea B.
Abstract: Objectives: To systematically assess the literature examining the association between foot disease (foot ulceration, infection, critical ischaemia and/or Charcot neuroarthropathy) and physical function in older adults. Methods: Literature search of MEDLINE, Embase and CINAHL was performed. Studies were included if foot disease and physical function were assessed in participants of mean or median age ≥ 65 years. Results: Of 2, 574 abstracts screened, 19 studies (13 longitudinal, 6 cross‐sectional) reporting on 5634 participants, 43% female, were included. Diabetes‐related foot disease and critical ischaemia were most studied (n = 5017, 40% female). In 8 studies with control groups, foot disease was associated with poorer physical function. Meta‐analysis of 5 studies (n = 1503, 45% female) found an association between foot disease and poorer physical function (SMD (95% CI): 1.00 (0.40, 1.62), P < 0.001). Conclusion: Foot disease is associated with poorer physical function in older adults. Future research should include broader study populations and intervention strategies.